Oral History Program Interview: Byrd Monford Morgan - Morgan, Byrd Monford
CALIFORNIA STATE COLLEGE, BAKERSFIELD CALIFORNIA ODYSSEY The 1930s Migration to the Southern San Joaquin Valley Oral History Program Interview Between INTERVIEWEE: Byrd Monford Morgan PLACE OF BIRTH: Council Hill, Muskogee County, Oklahoma INTERVIEWER: Stacey Jagels